Eisenhower's nuclear calculus in Europe : the politics of IRBM deployment in NATO nations - Brown, Gates M. (McFarland & Company, Inc., Publishers, 2018)
"Through a reliance on nuclear weapons, President Eisenhower hoped to provide a defense strategy that would allow the U.S. to maintain its security requirements without creating an economic burden. The U.S. required European missile bases to deploy its intermediate range ballistic missiles. Deploying such missiles to Europe required balancing regional European concerns with U.S. domestic security priorities."--